COMPARATIVE ANALYSIS OF THE IMPLEMENTATION OF STUNTING REDUCTION POLICY (CASE STUDY OF KUANTAN SINGINGI AND ROKAN HULU REGENCIES) - Rika Meriza; Harapan Tua RFS (PT. Jurnal Center Indonesia Publisher, 2026)
Stunting is a chronic nutritional problem threatening Indonesia’s human resource quality. Although the government issued, implementation shows results across regions. This research analyzes and compares stunting reduction policy implementation in Kuantan Singingi and Rokan Hulu Regencies, Riau Province, using George Edward III’s policy implementation theory. This qualitative research with comparative case study approach employs in interviews, observation, and documentation. Results show both regencies face different challenges in communication, resources, disposition, and bureaucratic structure. Kuantan Singingi experienced increased stunting prevalence from 17.8% (2022) to 23% (2023), while Rokan Hulu successfully reduced from 58.9% (2013) to 17.9% (2021). Implementation success differences are caused by variations in cross-sectoral coordination, resource adequacy, implementer commitment, and bureaucratic structure effectiveness.